Sita: warrior of Mithila : of the Ram Chandra series, Vol. II - Amish (Westland, 2017)
India, 3400 BCE. The ancient kingdom of Mithila is divided by corruption, resentment, and poverty. An abandoned baby is found in a field protected by a vulture from a pack of wolves. Soon adopted by the rulers of the land, she is named Sita, and raised as a princess and beloved daughter.